Identification Of An Antagonistic Actinomycete And Its Use In The - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
Eleven strains of Actinomycetes isolated from soils and potato periderm were screened for their antagonistic activities against the potato common scab pathogen, Streptomyces scabies. Strain 337 demonstrated the most significant activity in both the Cross-Streak and Cup Diffusion Agar tests. Based on the morphological and physiological characteristics, the strain was identified as Streptomyces violaceusniger. WB medium containing wheat bran 50 g, swine feces 10 g, Ca(OH)2 1 g, and moisture 50% was found to be a promising substrate for making a bioactinocide by principles of solid substrate fermentation. Pot bioassay showed that the ratio of scab incidence area was decreased to 6.7% using the bioactinocide, compared to 18.2% in control. The viable count of S. scabies in the bioactinocide pot decreased to 4.4 x 104from 1.6 x 106 CPU per gram soil by 12 weeks. There was also evidence of tuber yield increase to 12.4% in pots supplemented with the bioactinocide. Intisari Sebelas strain Aktinomisetes yang diisolasi dari tanah dan kulit kentang telah diuji daya antagonistiknya terhadap patogen penyakit kudis pada umbi kentang, Streptomyces scabies. Pada uji antagonisme dengan metode Cross-Streak dan Cup Diffusion Agar, strain 337 menunjukkan aktivitas yang paling tinggi.dibandingkan strain-strain yang lain. Berdasarkan ciri morfologi dan sifat fisiologinya, strain 337 di identifikasi sebagai Streptomyces violaceusniger. Medium WB yang tersusun atas sekam gandum 50 g, kotoran babi 10 g, Ca(OH),1 g, dan keiembaban 50% terbukti sebagai medium yang baik untuk .memproduksi bioaktinosida secara fermentasi substrat padat. Uji hayati pada pot menunjUkkan bahwa tingkat serangan penyakit kudis pada kontrol dan perlakuan bioaktinosida berturut-turut 18,2% dan 6,7%. Bioaktinosida menekan populasi S. scabies dari 1,6 x 106 menjadi 4,4 x 104 CFU/g tanah selama inkubasi 12 minggu. Perlakuan dengan bioaktinosida juga meningkatkan hasil umbi kentang sebesar 12,4% dibandingkan dengan kontrol.